Motivation-Building to Provide Quality Teaching through ICT-Based Training and Mentoring Sessions: A Case of Junior High School Teachers - Subekti, Adaninggar Septi; Lestariningsih, Fransisca Endang; Kurniawati, Lemmuela Alvita (Universitas Negeri Makassar, 2024)
The community service programme was designed and conducted in response to the need of the school partner, SMP Negeri 2 Purwosari Gunungkidul, to improve the motivation of the teachers to provide quality teaching for the low-motivated students. The programme lasted from February 2023 until November 2023 and was carried out in the form of training sessions and mentoring sessions. In total, there were four main activities in the programme: a motivation-building session intended to remind the teachers of the altruistic purposes of the profession, the writing-up of a module on how to utilise technological tools to motivate students, a training session on how to effectively use technological tools in the class instruction, and team-teaching sessions where we team-taught classes with selected three teachers using technological tools to engage students in class. Though throughout the programme there were challenges on our part and the teachers, generally the programme was a success. The programme evaluation suggested that teachers were generally satisfied with the programme and were more confident in using technology in teaching. Future similar programmes can be conducted with school partners sharing similar characteristics with those of our present school partner, to allow a higher quality of class instruction and eventually students' learning.